Development of Environmentally Friendly Technology for Key Industries in Achieving Golden Indonesia - Ramadhan, Muhammad Luthfi; Nugraha, Fajar; Prastowo, Dwi Ady; Kusumawardhani, Amie; Raharjo, Susilo Toto (LifeSciFi, 2024)
Indonesia aims for Golden Indonesia 2045, combining economic prosperity, social justice, and environmental sustainability. Facing challenges like deforestation, pollution, and climate change, sustainable development is urgent. Developing eco-friendly technology in areas like renewable energy, waste management, sustainable agriculture, and manufacturing is key for growth while addressing these challenges. This research aims to identify and analyze the development of environmentally friendly technology that can support key industries in achieving the vision of a Golden Indonesia 2045. The research methods used include literature studies, secondary data analysis, and interviews with industry experts and environmental experts. The analysis results show that the development of environmentally friendly technology is a strategic step that supports the vision of Golden Indonesia 2045, which emphasizes sustainable and environmentally sound economic growth. Various technologies such as renewable energy, waste management, energy efficiency and sustainable transportation are the main focus in achieving this goal. The findings of this research provide an important contribution to the understanding of the role of environmentally friendly technology in industrial transformation towards a Golden Indonesia 2045.